2014
DOI: 10.2459/jcm.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of peripartum cardiomyopathy in the United States

Abstract: An abnormal profile in serum adipokines observed in AMI is related to systemic inflammation and the degree of atherosclerosis independently of glucose metabolism disturbances and heralds major adverse cardiovascular event occurrence in long-term observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…24,25 Peripartum cardiomyopathy risk factors include maternal age >30 years, African ancestry, multiparity, multigestation, preeclampsia/eclampsia, anemia, diabetes, obesity, and prolonged tocolysis. 22,23,26–30 A genetic contribution is recognized, 31–33 particularly titan gene mutations. 34,35 Most women present with HF within 1 month postpartum; cardiogenic shock, arrhythmias, or venous-arterial thromboembolism are all possible.…”
Section: Special Populationsmentioning
confidence: 99%
“…24,25 Peripartum cardiomyopathy risk factors include maternal age >30 years, African ancestry, multiparity, multigestation, preeclampsia/eclampsia, anemia, diabetes, obesity, and prolonged tocolysis. 22,23,26–30 A genetic contribution is recognized, 31–33 particularly titan gene mutations. 34,35 Most women present with HF within 1 month postpartum; cardiogenic shock, arrhythmias, or venous-arterial thromboembolism are all possible.…”
Section: Special Populationsmentioning
confidence: 99%
“…In overall analysis, circulating apelin concentration was significantly lower in CAD patients than in controls (WMD: -1.285 ng/mL, 95% CI: -1.790 to -0.780, P < 0001), while statistical heterogeneity was significant ( I 2 : 99.3%, P < 0.001) (Figure 1 : the UPPER panel). As two studies involved controls with atrial fibrillation [ 13 ] and stable angina [ 21 ], respectively, a sensitivity analysis by excluding the two studies found the reduction in circulating apelin concentration was still significant (WMD: -1.465 ng/mL, 95% CI: -2.024 to -0.906, P < 0001), with significant heterogeneity ( I 2 : 99.3%, P < 0.001). The cumulative and influential analyses were displayed in Supplementary Figure S2 .…”
Section: Resultsmentioning
confidence: 99%
“…In patients undergoing cardiothoracic surgery, the levels of resistin were correlated with oxidative stress and myocardial injury [38]. In a recently published paper, resistin was considered to be an independent risk factor of recurrent AMI/unstable angina among patients with coronary artery disease [39]. In study by Takata et al .…”
Section: Discussionmentioning
confidence: 99%